2003
DOI: 10.1172/jci200317166
|View full text |Cite
|
Sign up to set email alerts
|

Disabling an integral CTL epitope allows suppression of autoimmune diabetes by intranasal proinsulin peptide

Abstract: Insulin is a major target of the autoimmune response associated with destruction of pancreatic β cells in type 1 diabetes. A peptide that spans the junction of the insulin B chain and the connecting (C) peptide in proinsulin has been reported to stimulate T cells from humans at risk for type 1 diabetes and autoimmune diabetes–prone NOD mice. Here we show that proinsulin B24–C36 peptide binds to I-Ag7, the MHC class II molecule of the NOD mouse, and, after intranasal administration, induces regulatory CD4+ T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 37 publications
(16 reference statements)
3
32
0
Order By: Relevance
“…The interpretation and prediction of responses to treatment and of mechanistic studies, especially T-cell studies, is heavily dependent on knowing the HLA status. As recently shown in mouse studies, the administration of a proinsulin peptide may elicit a population of regulatory CD4 T cells, but binding of the same peptide to class I molecules stimulated a cytotoxic CD8 T-cell response (36). This study showed the importance of characterizing binding of potentially therapeutic peptides to both class II and class I molecules to identify those peptides that, depending on HLA genotypes at the main class II and class I loci, are more likely to have therapeutic effects and less likely to promote disease activity.…”
Section: Summary Of 14th Ihiws Discussionmentioning
confidence: 74%
“…The interpretation and prediction of responses to treatment and of mechanistic studies, especially T-cell studies, is heavily dependent on knowing the HLA status. As recently shown in mouse studies, the administration of a proinsulin peptide may elicit a population of regulatory CD4 T cells, but binding of the same peptide to class I molecules stimulated a cytotoxic CD8 T-cell response (36). This study showed the importance of characterizing binding of potentially therapeutic peptides to both class II and class I molecules to identify those peptides that, depending on HLA genotypes at the main class II and class I loci, are more likely to have therapeutic effects and less likely to promote disease activity.…”
Section: Summary Of 14th Ihiws Discussionmentioning
confidence: 74%
“…A major problem is the selection of candidate peptides, which must be strongly immunogenic and be able to induce the desired T-cell response. Different strategies have included modifying amino acid residues on candidate epitopes in a proinsulin peptide to induce either regulatory CD4 1 or cytotoxic CD8 1 T cells in non-obese diabetic mice (95,96). If observations from studies of autoepitopes on lupus antigens apply to cancer, it would be important to identify regions of TAAs that are recognized by the immune system of the patient, taking this response to indicate realistic in vivo targets and to design immunotherapy directed at such autoepitopes.…”
Section: Discussionmentioning
confidence: 99%
“…The findings reported by Martinez et al (18) suggest that the undetected induction of CD8 + T cell responses could explain at least some of the contrasting outcomes reported by several experimental studies and clinical trials. Most importantly, this study has practical implications for the design of clinical trials based on the administration of peptides for preventing autoimmunity.…”
Section: The Double-edged Swordmentioning
confidence: 98%
“…In the current issue of the JCI, Martinez et al report on a new element that will need to be considered when attempting peptide-based T1D therapy (18). While the goal of peptide administration is to induce regulatory cells and inhibit specific autoimmune responses, the data show that, depending on the peptide used, one may also induce undesired cytotoxic CD8 + T cell responses.…”
Section: The Double-edged Swordmentioning
confidence: 99%